The Use of Artificial Intelligence in the Integration for Process Intelligence Data Sources Analysis - Ronitua, Justinus (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Integrating and analyzing intelligent data is a significant challenge in a digital age characterized by abundant data from various sources. The application of Artificial Intelligence (AI) offers a potential solution to address this complexity. This article explores AI's role in analyzing the integration of intelligence data sources, highlighting its benefits, challenges, and implications for strategic decision-making. The main problem to be addressed in this study is how AI can assist in the intelligence integration analysis process. The method used in this research is a qualitative method based on a literature review. The result of this study is that there are at least 4 (four) mechanisms of Artificial Intelligence (AI) utilization in analyzing the integration of intelligence data sources, namely machine learning mechanisms, search methods and optimization theory, knowledge-based and reasoning, and decision-making algorithms. Evaluation of AI implementation must be accompanied by attention to security challenges, ethics, and technological limitations. With the right approach, AI can be a powerful tool in supporting strategic decision-making and maintaining national security.